2009
DOI: 10.1186/1710-1492-5-10
|View full text |Cite
|
Sign up to set email alerts
|

Urticaria and infections

Abstract: Urticaria is a group of diseases that share a distinct skin reaction pattern. Triggering of urticaria by infections has been discussed for many years but the exact role and pathogenesis of mast cell activation by infectious processes is unclear. In spontaneous acute urticaria there is no doubt for a causal relationship to infections and all chronic urticaria must have started as acute. Whereas in physical or distinct urticaria subtypes the evidence for infections is sparse, remission of annoying spontaneous ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
138
0
30

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(184 citation statements)
references
References 99 publications
9
138
0
30
Order By: Relevance
“…In 2009, Wedi et al (3) reported the benefits of the eradication of this bacteria in patients with ChU in 13 studies (including a total of 322 patients), against 9 studies (164 patients) showing no benefits. In the studies that demonstrated the treatment to be beneficial, 84% of the patients showed either significant improvement or complete remission of the ChU after the bacterial eradication, in contrast with 45% of the patients who were infected but not treated, and 29% of the noninfected and not treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2009, Wedi et al (3) reported the benefits of the eradication of this bacteria in patients with ChU in 13 studies (including a total of 322 patients), against 9 studies (164 patients) showing no benefits. In the studies that demonstrated the treatment to be beneficial, 84% of the patients showed either significant improvement or complete remission of the ChU after the bacterial eradication, in contrast with 45% of the patients who were infected but not treated, and 29% of the noninfected and not treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria is a mucocutaneous disease characterized by erythematous, edematous and pruritic lesions of the dermis and/or hypodermis, resulting from the degranulation of mast cells and basophils and the release of inflammatory mediators, mainly histamine (1)(2)(3)(4) . It affects from 15 to 25% of the population at some stage of life, and is classified as acute (lesions lasting less than six weeks) or chronic, when the lesions last for more than six weeks, either daily or on most days of the week (1) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations